Модифіковані ресурсно-календарні моделі - сучасні інструменти управління реалізацією будівельного проекту - Лилов, О. В. (Ways to Improve Construction Efficiency, 2013)
This article is devoted to the problem of updating organizational and technological models of organization management, customer resource developer in the construction project. A fundamentally new type of resource calendar model building project, to reliably assess the readiness of organizations participating in the project implementation plan in line with customer and truly consider the impact of the external environment of the furniture project. The model was developed as a tool for sustainable management of construction project developer and have overcome significant project risks in property development scheme of construction.